Analysis of second-generation epigenetic clocks reveals further associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Vincent Doré; Pierrick Bourgeat; Rosita Shishegar; James D. Doecke; Paul Maruff; Christopher C. Rowe; Victor L. Villemagne; Michael Weiner; Paul Aisen; Ronald Petersen; et al. (GeroScience, 2026)

Cognition as a Conservation Tool: A Case Study of Florida Manatees and Boat Strikes - Gordon B. Bauer; Charles J. Deutsch; Roger L. Reep; Wendi Fellner; Tabitha Gunnars; Peter F. Cook; Heidi E. Harley; Athena M. Rycyk (Marine Mammal Science, 2026)
Boat strikes injure and kill large numbers of Florida manatees ( Trichechus manatus latirostris ) each year. Management actions taken to mitigate this threat can be potentially enhanced by consideration of manatee cognitive processes. The role of cognition in marine mammal conservation has received little consideration in the literature. Here, we integrate discoveries from laboratory research on auditory sensory processes and perception with findings from field studies of how manatees respond to motorized vessels and the effect of the ambient soundscape on response times to boat noise. We incorporate that information into recommendations for manatee management to further reduce the risk of collisions. We also suggest lines of research to investigate other relevant cognitive issues—including attention, learning, memory, and decision‐making—to improve conservation efforts and understanding of manatee behavior.

Exploring Marine Mammal Cognition as a Conservation Tool - Gordon B. Bauer; Peter F. Cook; Heidi E. Harley; Jason Bruck; Mel Cosentino; Charles J. Deutsch; Nicola Erdsack; Wendi Fellner; Tabitha Gunnars; Heather Manitzas Hill; Sonia V. Kumar; Malin K. Lilley; et al. (Marine Mammal Science, 2026)
Cognition is an animal's real‐time adaptation system for responding to change. Rapid environmental change, often anthropogenic, is expanding the range and severity of challenges confronting wild animals. Effective conservation requires a multifaceted approach that includes animals' capacities. Large‐brained, long‐lived animals such as marine mammals often have extensive capability to adaptively modify their behavior due to their cognition, which comprises the mechanisms of information acquisition, processing, and flexible action. Consequently, current behavior need not be a final predictor of future behavior for these animals. This flexibility provides an underutilized and under examined point of leverage for humans interested in improving life outcomes for wild animals. In this team‐written, interdisciplinary paper, we argue that application of cognitive approaches may facilitate many conservation efforts directed toward marine mammals. Starting with a workshop on this topic at the 24th Biennial Conference on the Biology of Marine Mammals, scientists representing a wide range of disciplinary expertise addressed eight different conservation concerns for six marine mammal species and provided potential cognitive explanations of and interventions aimed at related behavior. Our treatment highlights the value of integrated laboratory and field research, and the importance of tight lines of communication between scientists and conservation managers.

Surface-based morphometry reveals divergent aging trajectories in veterans with and without traumatic brain injury - Michelle C. Eliason; Amrutha Bindu Nagella; Cristian Cuadra; David S. Wack; Ghazala T. Saleem; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowki; Arthur W. Toga; et al. (GeroScience, 2025)

Voxel-wise insights into early Alzheimer’s disease pathology progression: the association with APOE and memory decline - Maha Wybitul; Nicolas Langer; Christoph Hock; Anton Gietl; Valerie Treyer; Michael Weiner; Paul Aisen; Ronald-Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; et al. (GeroScience, 2025)
Longitudinal investigation of the Apolipoprotein E (APOE) genotype’s impact on Alzheimer’s disease (AD) biomarker progression, focusing on amyloid beta (Aβ) accumulation and gray matter (GM) atrophy, integrating cognitive decline and baseline levels. Longitudinal florbetapir-PET and T1-weighted MRI data from 100 cognitively normal (CN) and mild cognitive impaired (MCI) participants both with considerable global Aβ accumulation (“high Aβ accumulators”) were analyzed using a voxel-wise approach. Associations of APOE genotype and memory decline with Aβ accumulation and GM atrophy were examined separately for each neuroimaging modality, controlling for baseline Aβ levels and diagnosis. Alternatively, the effect of baseline diagnosis, while controlling for memory decline, was investigated. A multimodal analysis evaluated interactions between genotype, memory decline, and GM atrophy on Aβ accumulation. High Aβ accumulators displayed extensive Aβ pathology predominantly in the medial orbito-frontal cortex, cingulate cortex, and precuneus, along with GM atrophy in temporal, occipital, orbito-frontal, and parietal areas. ɛ4 carriers with memory decline exhibited greater Aβ accumulation and GM atrophy in selective regions compared to non-carriers with memory decline, while no genotype difference was observed in individuals without decline. No interaction effect was observed for MCI diagnosis. Regional associations between the two biomarkers were similarly dependent on genotype and memory decline. ɛ4 carriers exhibiting memory decline present an accelerated neurobiological pattern at predementia stages, supporting early ɛ4 carrier monitoring and interventions in this at-risk group. Importantly, memory decline might be more informative than MCI regarding AD pathology progression emphasizing the importance of repeated cognitive assessments.

In depth study of conidial morphology of Erysiphe alphitoides on Wisteria species reveals characteristics of a self-blocking chance host - Roger T. A. Cook; Uwe Braun; Michael Bradshaw; Geoffrey J. Denton; Jennifer O. Denton (Journal of Plant Pathology, 2025)

Dynamic proportional loss of functional connectivity revealed change of left superior frontal gyrus in subjective cognitive decline: an explanatory study based on Chinese and Western cohorts - Luyao Wang; Wenjing Hu; Fan Dong; Can Sheng; Jinglong Wu; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2025)

Dietary Fiber Intake and Risk of Advanced and Aggressive Forms of Prostate Cancer: A Pooled Analysis of 15 Prospective Cohort Studies - Elkhansa Sidahmed; Stephen J. Freedland; Molin Wang; Kana Wu; Demetrius Albanes; Matt Barnett; Piet A. van den Brandt; Michael B. Cook; Graham G. Giles; Edward Giovannucci; Christopher A. Haiman; Susanna C. Larsson; et al. (Journal of the Academy of Nutrition and Dietetics, 2025)

Complementary value of molecular, phenotypic, and functional aging biomarkers in dementia prediction - Andreas Engvig; Karl Trygve Kalleberg; Lars T. Westlye; Esten Høyland Leonardsen; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; et al. (GeroScience, 2024)
DNA methylation age (MA), brain age (BA), and frailty index (FI) are putative aging biomarkers linked to dementia risk. We investigated their relationship and combined potential for prediction of cognitive impairment and future dementia risk using the ADNI database. Of several MA algorithms, DunedinPACE and GrimAge2, associated with memory, were combined in a composite MA alongside BA and a data-driven FI in predictive analyses. Pairwise correlations between age- and sex-adjusted measures for MA (aMA), aBA, and aFI were low. FI outperformed BA and MA in all diagnostic tasks. A model including age, sex, and aFI achieved an area under the curve (AUC) of 0.94 for differentiating cognitively normal controls (CN) from dementia patients in a held-out test set. When combined with clinical biomarkers (apolipoprotein E ε4 allele count, memory, executive function), a model including aBA and aFI predicted 5-year dementia risk among MCI patients with an out-of-sample AUC of 0.88. In the prognostic model, BA and FI offered complementary value (both β s 0.50). The tested MAs did not improve predictions. Results were consistent across FI algorithms, with data-driven health deficit selection yielding the best performance. FI had a stronger adverse effect on prognosis in males, while BA’s impact was greater in females. Our findings highlight the complementary value of BA and FI in dementia prediction. The results support a multidimensional view of dementia, including an intertwined relationship between the biomarkers, sex, and prognosis. The tested MA’s limited contribution suggests caution in their use for individual risk assessment of dementia.

Local molecular and connectomic contributions of tau-related neurodegeneration - Fardin Nabizadeh; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; John Q. Trojanowski; Arthur W. Toga; Laurel Beckett; Robert C. Green; Andrew J. Saykin; John Morris; et al. (GeroScience, 2024)

Remission cytochrome spectroscopy reveals the mode of action of bedaquiline in living mycobacteria - Suzanna H. Harrison; Rowan C. Walters; Morwan M. Osman; Roger J. Springett; Gregory M. Cook; James N. Blaza (Biochimica et Biophysica Acta (BBA) - Bioenergetics, 2024)

Sex differences in interacting genetic and functional connectivity biomarkers in Alzheimer’s disease - Jordan N. Williamson; Shirley A. James; Sean P. Mullen; Bradley P. Sutton; Tracey Wszalek; Beni Mulyana; Peter Mukli; Andriy Yabluchanskiy; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2024)

Glucose metabolism in posterior cingulate cortex has supplementary value to predict the progression of cognitively unimpaired to dementia due to Alzheimer’s disease: an exploratory study of 18F-FDG-PET - Qi Zhang; Chunqiu Fan; Luyao Wang; Taoran Li; Min Wang; Ying Han; Jiehui Jiang; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2023)

Glucose metabolism patterns: A potential index to characterize brain ageing and predict high conversion risk into cognitive impairment - Jiehui Jiang; Can Sheng; Guanqun Chen; Chunhua Liu; Shichen Jin; Lanlan Li; Xueyan Jiang; Ying Han; Michael W. Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2022)

Comprehensive analysis of epigenetic clocks reveals associations between disproportionate biological ageing and hippocampal volume - Lidija Milicic; Michael Vacher; Tenielle Porter; Vincent Doré; Samantha C. Burnham; Pierrick Bourgeat; Rosita Shishegar; James Doecke; Nicola J. Armstrong; Rick Tankard; Paul Maruff; Colin L. Masters; et al. (GeroScience, 2022)
The concept of age acceleration, the difference between biological age and chronological age, is of growing interest, particularly with respect to age-related disorders, such as Alzheimer’s Disease (AD). Whilst studies have reported associations with AD risk and related phenotypes, there remains a lack of consensus on these associations. Here we aimed to comprehensively investigate the relationship between five recognised measures of age acceleration, based on DNA methylation patterns (DNAm age), and cross-sectional and longitudinal cognition and AD-related neuroimaging phenotypes (volumetric MRI and Amyloid-β PET) in the Australian Imaging, Biomarkers and Lifestyle (AIBL) and the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Significant associations were observed between age acceleration using the Hannum epigenetic clock and cross-sectional hippocampal volume in AIBL and replicated in ADNI. In AIBL, several other findings were observed cross-sectionally, including a significant association between hippocampal volume and the Hannum and Phenoage epigenetic clocks. Further, significant associations were also observed between hippocampal volume and the Zhang and Phenoage epigenetic clocks within Amyloid-β positive individuals. However, these were not validated within the ADNI cohort. No associations between age acceleration and other Alzheimer’s disease-related phenotypes, including measures of cognition or brain Amyloid-β burden, were observed, and there was no association with longitudinal change in any phenotype. This study presents a link between age acceleration, as determined using DNA methylation, and hippocampal volume that was statistically significant across two highly characterised cohorts. The results presented in this study contribute to a growing literature that supports the role of epigenetic modifications in ageing and AD-related phenotypes.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

A role for artificial night-time lighting in long-term changes in populations of 100 widespread macro-moths in UK and Ireland: a citizen-science study - John Fawcett Wilson; David Baker; Janet Cheney; Mike Cook; Martin Ellis; Roger Freestone; David Gardner; Graham Geen; Robin Hemming; Don Hodgers; Stephen Howarth; Ade Jupp; et al. (Journal of Insect Conservation, 2018)

Comparison of four modeling tools for the prediction of potential distribution for non-indigenous weeds in the United States - Roger Magarey; Leslie Newton; Seung Cheon Hong; Yu Takeuchi; David Christie; Catherine S. Jarnevich; Lisa Kohl; Martin Damus; Steven I. Higgins; Leah Millar; Karen Castro; Amanda West; et al. (Biological Invasions, 2018)

A longitudinal study of patients with cirrhosis treated with L-ornithine L-aspartate, examined with magnetization transfer, diffusion-weighted imaging and magnetic resonance spectroscopy - Vijay P. B. Grover; Mark J. W. McPhail; Marzena Wylezinska-Arridge; Mary M. E. Crossey; Julie A. Fitzpatrick; Louise Southern; Brian K. Saxby; Nicola A. Cook; I. Jane Cox; Adam D. Waldman; Novraj S. Dhanjal; Aluel Bak-Bol; et al. (Metabolic Brain Disease, 2017)

Climate association with fluctuation in annual abundance of fifty widely distributed moths in England and Wales: a citizen-science study - John Fawcett Wilson; David Baker; Mike Cook; George Davis; Roger Freestone; David Gardner; Dave Grundy; Norman Lowe; Steve Orridge; Heather Young (Journal of Insect Conservation, 2015)

The OsGEX2 Gene Promoter Confers Sperm Cell Expression in Transgenic Rice - Meridith Cook; Roger Thilmony (Plant Molecular Biology Reporter, 2012)

The “salt wedge pump”: Convection‐driven pore‐water exchange as a source of dissolved organic and inorganic carbon and nitrogen to an estuary - Isaac R. Santos; Perran L. M. Cook; Louissa Rogers; Jason de Weys; Bradley D. Eyre (Limnology and Oceanography, 2012)
Hypoxia and anoxia in coastal waters have typically been explained by the respiration of sinking organic matter associated with nutrient over‐enrichment and phytoplankton blooms. Here, we assess whether submarine groundwater discharge and seawater recirculation in sediments can explain widespread chemical anomalies, including low dissolved oxygen, in salt wedge estuaries. We rely on high‐resolution radon (a natural groundwater and pore‐water tracer), and dissolved carbon concentrations and stable isotope observations in the Yarra River estuary in Melbourne, Australia. Radon was highly enriched within the salt wedge, demonstrating enhanced pore‐water exchange at this area. We use the term “salt wedge pump” to describe convection‐driven advective pore‐water exchange at the sediment–water interface during the upstream propagation of the salt wedge. Radon‐derived convection‐driven pore‐water exchange rates within the salt wedge were estimated at 2.8 cm d −1 , a value equivalent to 2.4% of the total river freshwater runoff to the estuary. Pore‐water exchange led to pulsed dissolved inorganic carbon (DIC) and ammonium fluxes ∼ 10‐fold higher than measured diffusive fluxes. In contrast, diffusive sediment oxygen uptake was 5‐fold higher than oxygen uptake related to advective pore‐water exchange. Estimated fluxes, associated with the nonconservative DIC, δ 13 C‐DIC, and ammonium behavior within the estuary support convective pore‐water exchange as a major source of DIC and ammonium to the estuary, but not of dissolved organic carbon, nitrate, dissolved organic nitrogen, and anoxia. Accounting for seawater recirculation in sediments may help reconcile unbalanced carbon and nitrogen budgets in several coastal systems.

Haplotype structure in Ashkenazi Jewish BRCA1 and BRCA2 mutation carriers - Kate M. Im; Tomas Kirchhoff; Xianshu Wang; Todd Green; Clement Y. Chow; Joseph Vijai; Joshua Korn; Mia M. Gaudet; Zachary Fredericksen; V. Shane Pankratz; Candace Guiducci; Andrew Crenshaw; et al. (Human Genetics, 2011)

Microcyclic conidiogenesis in powdery mildews and its association with intracellular parasitism by Ampelomyces - Levente Kiss; Alexandra Pintye; Györgyi Zséli; Tünde Jankovics; Orsolya Szentiványi; Yaser M. Hafez; Roger T. A. Cook (European Journal of Plant Pathology, 2010)

PQLI Key Topics - Criticality, Design Space, and Control Strategy - Thomas Garcia; Graham Cook; Roger Nosal (Journal of Pharmaceutical Innovation, 2008)

Effects of a plant parasitic nematode (Heterodera trifolii) on clover roots and soil microbial communities - Amy M. Treonis; Roger Cook; Lorna Dawson; Susan J. Grayston; Tony Mizen (Biology and Fertility of Soils, 2007)

Analysis of referrals to a multi-disciplinary breast cancer genetics clinic: practical and economic considerations - Marta M. Reis; Dorothy Young; Lorna McLeish; David Goudie; Alan Cook; Frank Sullivan; Helen Vysny; Alison Fordyce; Roger Black; Manouche Tavakoli; Michael Steel (Familial Cancer, 2006)

The effect of polymorphism at the serotonin transporter gene on decision-making, memory and executive function in ecstasy users and controls - Jonathan P. Roiser; Robert D. Rogers; Lynnette J. Cook; Barbara J. Sahakian (Psychopharmacology, 2006)

Phylogeny and taxonomy of powdery mildew fungi of Erysiphe sect. Uncinula on Carpinus species - Uwe Braun; Susumu Takamatsu; Vasyl Heluta; Saranya Limkaisang; Rangsi Divarangkoon; Roger Cook; Herbert Boyle (Mycological Progress, 2006)

Temporal resolution of the Florida manatee (Trichechus manatus latirostris) auditory system - David A. Mann; Debborah E. Colbert; Joseph C. Gaspard; Brandon M. Casper; Mandy L. H. Cook; Roger L. Reep; Gordon B. Bauer (Journal of Comparative Physiology A, 2005)

Selective antagonism of the ataxic effects of zolpidem and triazolam by the GABA A /α 1 -preferring antagonist β-CCt in squirrel monkeys - Donna Platt; James Rowlett; Roger Spealman; James Cook; Chunrong Ma (Psychopharmacology, 2002)

Role of GABA A /benzodiazepine receptors containing α 1 and α 5 subunits in the discriminative stimulus effects of triazolam in squirrel monkeys - Snjezana Lelas; James Rowlett; Roger Spealman; James Cook; Chunrong Ma; Xiaoyan Li; Wenyuan Yin (Psychopharmacology, 2002)

Stability in the historical pattern of genetic structure of Newfoundland cod (Gadus morhua) despite the catastrophic decline in population size from 1964 to 1994 - Daniel E. Ruzzante; Christopher T. Taggart; Roger W. Doyle; Doug Cook (Conservation Genetics, 2001)

The influence of nematodes on below-ground processes in grassland ecosystems - Richard D. Bardgett; Roger Cook; Gregor W. Yeates; Crystal S. Denton (Plant and Soil, 1999)

Axon guidance and somites - David Tannahill; Geoff M. W. Cook; Roger J. Keynes (Cell and Tissue Research, 1998)

Axon guidance and somites - David Tannahill; Geoff M. W. Cook; Roger J. Keynes (Cell and Tissue Research, 1997)

Abstracts of presentations on plant protection issues at the fifth international Mango Symposium Abstracts of presentations on plant protection issues at the Xth international congress of Virology - J. E. Peña; M. Wysoki; Gajendra Singh; Nancy Boscán de M.; Freddy J. Godoy; A. Obligado; C. J. Rossetto; I. J. A. Ribeiro; P. B. Gallo; N. B. Soares; J. C. Sabino; A. L. M. Martins; et al. (Phytoparasitica, 1997)